Approbation results of technique «diagnostics of psychological well-being of a person» (DPBO) - Kargina, N. V. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2017)
In the article the problem of diagnosing the peculiarities of psychological well-being on the basis of its structural components is observed. The relevance of the study phenomenon is expressed, above all, the need to identify and explain the individual psychological characteristics of a psychologically safe person that is able to defend their position in life, overcoming obstacles; to function in society, live in harmony with oneself and the world, capable of personal development and self-improvement. The results of testing of the author’s technique of «Diagnosis of psychological well-being of the individual» (DPBO). The results of testing this technique on the diagnostic value of all the requirements of psychometrics that showed sufficient degree of reliability and validity. The methodology of the study of the essential characteristics of the psychological well-being based on a conceptual view of the authors who have studied this perspective, as well as the peculiarities of diagnostics instruments – «Scale of psychological well-being C. Ryff», adaptation T.D. Shevelenkova and P.P. Fesenko, the technique «Eudemonic scale well-being» by A.S. Waterman, technique «Scale of mental well-being» Warwick-Edinburgh Mental Well-being Scale (WEMWBS)», the method of «General psychological wellbeing index» by H.J. Dupuy. Summing up the above said it should be noted that the features of psychological well-being of the individual can be studied not only in the scientific literature, but also in the empirically-practical aspect, referring to the different approaches of creating diagnostics instruments. Thus, the data complement the well-known theoretical and empirical foundations for the study of this phenomenon. Created by our method can be used for the production of psychological diagnosis, psychological correction and scientific study of individual features of the severity of psychological well-being of the individual.